Ethnobotanical and economic uses of some medicinal plants from native saline areas - Muneeb, Ahmed; Ahmad, Iftikhar; Ahmad, Muhammad Sajid Aqeel; Fatima, Sana; Hameed, Mansoor; Ahmad, Farooq; Asghar, Ansa; Basharat, Sana; Shah, Syed Mohsan Raza; Shafqat, Jazab; Hassan, Islam Frahat Zaky (International Journal of Applied and Experimental Biology, 2023)
Man is using plants for curing different diseases for several hundred years. In Pakistan, rangelands and forests are the major sources of medicinal plants, and the residents of different areas including those of the Vanhar Valley depend upon local plants for the medication of several diseases. However, this study was planned to enlist the indigenous medicinally important flora, which will help in conservation of the vanishing knowledge about the indigenous plants of the area by proper documentation. In order to document the uses of indigenous plants, some surveys were conducted for the collection of all available species. For the documentation of uses of these indigenous plant species, 55 experts were interviewed and their knowledge was documented. A total of 41 species belonging to 25 families were recorded from the Vanhar Valley. High numbers of species of families Fabaceae, Amaranthaceae and Asteraceae were used for the cure of several diseases like sexual disorders, piles, asthma, sputum, stomach disorders, diabetes, etc. It was evident that the older people had most of the knowledge about the indigenous plants of the Valley, while the young lacked such knowledge due to the death of older people without documenting or transferring the knowledge to them. With conservation of the knowledge, these plants can be used as a low-cost and effective treatment of many common diseases.